The evolution of Russian military doctrine in the post-Cold War period - أبو العبد, أحمد; عصام اسماعيل,; رامي كاسر لايقة , (Latakia University Journal - Economic and Legal Sciences Series, 2023)
The Military Doctrine of the Russian Federation is one of the basic strategic planning documents in the Russian Federation and constitutes a system of views and points of view officially approved by the state in preparation for the protection and armed defense of the Russian Federation. This research aims to study the general outlines of the documents of the Russian military doctrine in the post-Cold War phase, and to identify its most important developments, in addition to comparing these documents to find out the change in their content and to diagnose the nature of the actual and potential military threats and the nature of the future war in which Russia could be involved. Federal. The research reached a set of results, the most important of which are: The various Russian military doctrine documents, since the collapse of the Soviet Union, have expressed the reality of governance in Russia, the position of this country in the international system, its view of itself and its future, and the movement of other countries that compete with it in the international arena. By comparing the documents of the Russian military doctrine issued since 2000 up to the document of 2021, it becomes clear that there is a shift in Russia's military thought and this shift coincided with the change of ruling elites since the beginning of the twenty-first century with the arrival of new ruling elites with visions and aspirations based on the need to restore Russia to its global standing. Each military doctrine differed from the other in terms of content, by defining the sources of danger to the state, the forms of these dangers and threats, as well as in terms of the spiritual aspect of strategy, and what appears in it of the level of the state’s self-confidence and its ability to serve the goals set in the strategic planning for national security. The common denominator among the documents of the Russian military doctrine that Russia has applied since 2009 until now is its growing sense of existential danger from the expansion and approach of NATO to Russian territory.